The study of a socio-cultural phenomenon of capital - Manassova, M.M.; Seifullina, G.R.; Salymatova, N.R.; Razumov, V.I. (KU Publ., 2022)
The article is devoted the study of a socio-cultural phenomenon — Nur-Sultan. Its content reflects the views of focus group participants on important aspects of the study of the role of Nur-Sultan in the cultural and civilizational process: The socio-cultural features of the capital, the perception of the urban space of Nur-Sultan, intercultural communication. Nur-Sultan as a phenomenon becomes a subject of knowledge of the humanities where domestic scientists attach special significance to judgment of a role of the capital in public consciousness, to formation of patriotism and civil feelings and studied socio-cultural features of the capital, factors and mechanisms of the organization of cross-cultural communications. The new capital is represented the center which has to give an impetus to the economic growth of the country, overcome uneven placement of the population, fasten multiethnic structure of Kazakhstan, to become the city cosmopolitan. As a result of discussion, the impact of the capital on the political culture of youth and its social activity, young people’s views about the prospects and cultural significance of Nur-Sultan, the understanding of the interaction of scientific- technical, educational, political, artistic and aesthetic spheres of the organization of cultural process were identified.
Астананың социомәдени феноменін зерттеу
Исследование социокультурного феномена столицы
Keywords: city; capital; urbanization; culture; civilization; intercultural communication; Nur-Sultan